Research of Conditions of Economic Efficiency of Use of Composite Gasoline-Hydrogen Fuel - Mirzaabdullaev, Jakhongir B. (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we consider the analysis of data obtained by additional supply of hydrogen to the internal combustion engine as an additive to gasoline. The article presents the results of a study of the operating conditions of a passenger car using hydrogen as an additive to gasoline and determines the fuel consumption on the route of 100 km. Analysis of studies on the use of composite gasoline-hydrogen fuel for changing fuel consumption showed that the economic effect is observed and is 14,400 sum per day; 432,000 sum per month; 5,184,000 sum per year per vehicle. The revealed conditions of economic efficiency showed that when using composite gasoline- hydrogen fuel, significant economic efficiency is possible when used in urban passenger (taxi) transport.